Crimean Tatars during the famine of 1921–1923 - Grigory Kondratyuk (Крымское историческое обозрение)
Based on archival materials, the article considers one of the most tragic periods in the history of the Crimean peninsula – the famine of 1921–1923. Particular attention is paid to the Crimean Tatar population, as the most affected during this period. The article gives the number of those who died from starvation in different settlements and regions. The actions of the authorities aimed at preventing the catastrophic consequences of the famine are analyzed.